Pengaruh Waktu Sintering Pada Pembuatan Brakepad Dengan Matriks Phenolic Resin - Adrianto, Rizky (2016)
Brake is one component of a motor vehicle which serves to stop the vehicle speed motorcycle. When the rate of high-speed vehicle brake has an important role, even the safety of the rider depends on the quality of the brake lining. The purpose of this study was to compare the brake lining sintering temperature variations with a market canvass Indopart brands. Researchers will conduct research begins with making canvass sintering time varies with materials such as fiberglass, aluminum powder, brass powder, graphite, calcium carbonate, barium sulfate, and phenolic resin. After that mix the brake lining material in accordance with a predetermined composition. Then given the pressure while heated (sintering) with a load of 7.5 tons for 7 minutes with a variation of sintering time of 60 minutes, 90 minutes and 120 minutes, with a temperature of 200ºC. Then tested friction with a load of 15 kg for 60 minutes with dry test, spraying of water, with a standard testing SNI 09-2663-1992 then calculated wear and coefficient geseknya, and tested by using a Durometer hardness. From the research that the average wear of the brake lining Indopart lower and better than the brake with the sintering time variation in the friction test for 60 minutes. The coefficient of friction brake Indopart higher than the brake with the variation of sintering time on tests of friction for 60 minutes, the coefficient of friction Indopart high of 0.67 while that approach amounted to 0.63 on the brake with a variation of 60 minutes at a temperature of 200 ° C on a test dry , Hardness values Indopart brake better than the brake with the variation of sintering time of 94 Shore D, while the value of hardness approaching the brake with the variation of sintering time of 120 minutes with less sintering temperature of 200 ° C for 91 Shore D